The Influence of Workplace Spirituality, Commitment and Organizational Culture on Teacher Productivity - Wahib, Abd; Machfudz, Machfudz (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the influence of workplace spirituality and organizational culture on teacher productivity with organizational commitment as a mediating variable in madrasas. Seeing the problems and research objectives to be achieved, this study uses an explanative research approach with a survey approach. The questionnaire was compiled based on research variables: workplace spirituality, organizational culture, teacher productivity and organizational commitment. The research data was taken from 100 teachers who were the sample of this study. Data collection was carried out by using a random sampling technique. The data analysis uses the Partial Least Square (PLS) approach using Smart PLS software. The results of the hypothesis test show that workplace spirituality affects teacher productivity. The higher the workplace spirituality, the higher the teacher's productivity. Organizational culture influences teacher productivity. This means that the higher the organizational culture, the higher the teacher productivity. Teacher productivity affects organizational commitment. This means that the higher the teacher's productivity, the higher the organizational commitment. There is an indirect effect between workplace spirituality on teacher productivity through significant organizational commitment. In conclusion, the better the spiritual workplace and organizational culture, the more teacher productivity can increase, and the stronger the organizational commitment is supported.